RELATIONSHIP OF FAMILY ROLE WITH KNOWLEDGE OF YOUTH REPRODUCTIVE HEALTH IN DARMAIS HEALTH VOCATIONAL SCHOOL OF NURSING DEPARTMENT OF PADANGSIDIMPUAN 2018 - nelly karlinah (Excellent Midwifery Journal, 2019)
ABSTRACT Adolescence is a period of rapid growth and development both physically, psychologically and intellectually (Indonesian Ministry of Health, 2015). In the world, as many as 11% of pregnancies occur every year among adolescents (UNICEF, 2012). In Latin America and the Caribbean as many as 35-52% of adolescents experience unplanned pregnancies due to a lack of knowledge about pregnancy and menstruation (Aine & Maddaleno, 2003). Adolescent's knowledge about reproductive health is still low, this is evidenced by research conducted in Brazil that knowledge of puberty in 399 adolescents, as many as 57.6% were of low knowledge (Gomes, 2002). The purpose of the study was to determine the relationship of the role of families with knowledge of adolescent reproductive health in the Nursing Health Department of Darmais Padangsidimpuan Department. Type of analytic research with cross sectional approach, The sample in this study used the technique of "Total Sampling". Data were analyzed by univariate and bivariate using the Chi-Square test. The results of the univariate study showed that the majority of the roles of non-acting families were 24 people (68.6%) and the minority had a role of 11 people (31.4%). that the majority of poor adolescents' knowledge were 22 people (62.9%) and the Good minority were 13 people (37.1%). Bivariate research results P value = 0.003 means P value <0.05, which means that there is a relationship between the role of the family and knowledge of adolescent reproductive health in the health vocational department of nursing department at Darmais Padangsidimpuan Conclusion P value = 0.003 means P value <0.05, which means there is a relationship between the role of the family and knowledge of adolescent reproductive health in the nursing department of the nursing department of Darmais Padangsidimpuan. Keywords: Adolescent Reproductive Health, Family Role, Adolescent Knowledge